Pengaruh Kompensasi Dan Kepuasan Terhadap Kinerja Karyawan Cv. Kurnia Jaya Tekhnik - Nurriza, Muhammad Rosyid (PT. Kreasi Karya Majakata, 2023)
This study aims to investigate the effect of compensation and job satisfaction on employee performance at CV Kurnia Jaya Tekhnik. Quantitative research method on 30 samples with saturated sample technique. The results of data analysis show that work compensation has a positive and significant effect on employee performance partially. This indicates that an increase in compensation aspects such as salary, bonuses, and other incentives can improve employee performance in the company. In addition, job satisfaction also has a positive and significant influence on employee performance at CV Kurnia Jaya Tekhnik. These results highlight the importance of creating a positive work environment, providing career development opportunities, and ensuring effective communication between management and employees to improve job satisfaction. Simultaneously, work compensation and job satisfaction together have a positive and significant influence on employee performance simultaneously. This suggests that companies need to take an integrated approach in improving employee performance by paying attention to these two aspects